Hakim Perempuan Dalam Perspektif Hukum Islam (Posisi Hakim Perempuan Dalam Memutuskan Kasus Pidana Menurut Majlis Ulama Indonesia, Muhammadiyah dan Nahdlatul Ulama) - Nuruzzaman M. S., Nuruzzaman M. S.; , Prof. Dr. Absori, S.H., M.Hum; , DR. M. Muinudinillah (2015)
Leadership of women in islam is still a controversial issue. This is due to several factors, among others: first, the existence of texts (Qur‟an and Hadist) which textually implies virtue for men to be leaders. Secondly, dialectics is happening in the community, both the pros and cons of the position of woman judges. Third, the texts of the Qur‟an (QS.4:34) which indicates the primacy of men become the leader and prophet Muhammad hadits narrated by Abi Bakrah Companions who outwardly show that a people will not prosper if it is led by a women. Would however, some experts scholars allow it. From this views of scholars, will bring up a dialectic on the views of the scholars in Indonesia. For example in this context Majlis Ulama Indonesia (MUI), Ormas Muhammadiyah, and Nahdlatul Ulama as a spectrum of institutions into various ORMAS emphasizes the contextuality and does not apply to an harfiah understanding. Here the condition of women at the time (at the time of the prophet) has not allowed them to handle public affairs, because of lack of knowledge and experience. While at times it‟s a lot of women who have knowledge and experience about the affair. In response to the differences of opinion, the writer wants to give the title JUDGE LEGAL PERSPECTIVE OF WOMEN IN ISLAM (Judge Position of Women in Criminal Cases Decided According to MUI, Muhammadiyah and Nahdlatul Ulama). So in this study can be formulated as the following formulation of the problem; 1). How to Judge Position Position of Women in Criminal Cases Decided by the MUI, Muhammadiyah and Nahdlatul Ulama? 2). How does the concept of the future of women judges offered in deciding a criminal case? The method used in this study is a socio-historical method, and seeks to reconstruct istidlal or legal istinbath used MUI, Muhammadiyah and Nahdlatul Ulama systematically and objectively by collecting data and evaluating and mensistensikan proposition that will be used by the MUI, Muhammadiyah and Nahdlatul Ulama, in order to obtain a final conclusion in the context of the discourse ness. Based on the results of a study of MUI, Muhammadiyah and NU can be concluded that the law made istimbath three institutions based on konstektualitas thet does‟t apply to the literal understanding. In this context, the condition of women in itun time (at the time of the prophet) did‟t allow them to handle public affairs, due to lack of knowledge and experience, while today has a lot of women who have knowledge and experience on these matters